Efficiencies of Different Methods for Organophosphate Pesticide Residues Determination in Fermented Wheat Substrate - Đorđević, Tijana M; Šiler-Marinković, Slavica S; Đurović-Pejčev, Rada D; Dimitrijević-Branković, Suzana I; Gajić Umiljendić, Jelena S (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2013)
In present work comparison of efficiency of three different sample preparation methods for GC/MS determination of pirimiphos-methyl and chlorpyrifos-methyl residues in wheat (Triticum spelta) samples fermented by Lactobacillus plantarum was made. All three methods were based on methanol:acetone=1:1 extraction, while further purification of obtained samples was altered. First purification was through a column containing mixture of aluminium oxide and activated charcoal slurry-packed and eluted with dichlormethane, the second was purification on florisil column slurry-packed and eluted with ethil acetate:acetone=4:1, while the third was based on combination of first two mentioned methods, i.e. clean-up throught columns filled with mixture of aluminum oxide and activated charcoal slurry-packed and eluted with ethil acetate:acetone=4:1. The second method resulted to be the most effective for obtaining satisfactory recoveries at four fortification levels. For pirimiphos-methyl recoveries were in range of 91.3 – 96.0%, with good reproducibility i.e. RSD% in the range of 2.2 – 4.1%, while for chlorpyrifos-methyl were in range of 81.6 – 88.2%, with RSD% in the range of 2.5 – 5.4%. The chosen method was further optimized in order to establish the optimum volume of elution solvent used during the clean-up procedures. The highest recoveries of 93.7±3.5% for pirimiphos-methyl and 85.3±2.5% for chlorpyrifos-methyl were obtained after elution with 25 mL volume of solvent. Considering all, simple, efficient and reliable GC/MS detection of pirimiphos-methyl and chlorpyrifos-methyl residues from wheat grain substrate altered by fermentation with L. plantarum is achieved by two steps extraction with 25 mL of methanol:acetone=1:1 solvent mix for 30 min, followed by clean-up procedure through a glass column with florisil coupled with elution by 25 mL of ethyl acetate:acetone=4:1.